Analyzing The Implementation of Green-Economy Inclusive Strategy in East Java Province Through Urban Good Governance in Green-Economy Framework: The Case of Surabaya - Rizqi Shafira Chairunnisa; Hemalia Kusumadewi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
The global uncertainty has forced countries including Indonesia to look on ways to stabilize themselves, one of them being the implementation of green-economy development. The lack of inclusive and environmental-oriented policy has created an urgency for East Java Province to prioritize the green-economy implementation. Therefore this paper analyzes a possible implementation of green-economy through Surabaya City’s green-economy concept. This city is chosen due to its status being the only city in East Java to have the Green Sister City Surabaya-Kitakyushu program. This paper uses green economy city development which has four main dimensions which are; decision making process, Implementation Capacity, green economy system and the socio-ecological dimension. A qualitative-descriptive method will be used in this paper, along with a thematic analysis technique to deeply explain the topic at hand. The result of this research is a strategy that can be referenced by Surabaya to develop the green-economy city as the city already has its basis, especially in its society’s system in approaching green-economy aspects. Aside of that, this research also presents 3 strategies of implementing green-economy policies for cities throughout East Java Province. These strategies are intended for those cities to be able to take the first step in developing a green-economy city by deeper understanding of local context, policy & capacity development, and monitoring & evaluation.